THE FORMATION OF SURFACE LAYERS IN Zr-Fe ALLOYS UNDER ION IRRADIATION - Kirichenko, V. G.; Kobylnik, V. A.; Kovalenko, T. A.; Usatova, O. A. (East European Journal of Physics, 2017)
The study of phase transformations in intermetallic phases, which are released in the form of fine-dispersed inclusions in binary alloys based on zirconium Zr - 1.03 at. % Fe; Zr - 0.51 at. % Fe; after ion irradiation and subsequent isothermal annealing was carried out. Mössbauer spectroscopy on 57Fe nuclei in backscattering geometry with registration of internal conversion electrons, X-ray spectral analysis, X-ray diffraction analysis and electron microscopy were used. As a result, the observed segregation and phase composition of the intermetallic phases in the surface layer change under ion irradiation. Subsequent isothermal annealing after irradiation leads to a change in the concentration of inclusions of intermetallic phases and phase modification in the surface layer.